The Influence of Self Efficacy, Job Satisfaction and Organizational Commitment Toward Organizational Citizenship Behavior (Ocb) of Teachers Of Private Vocational Schools in South Jakarta - gati, kusumaninggati; Mukhtar, Mukhneri; Sujanto, Bedjo (International Journal of Scientific Research and Management (IJSRM), 2018)
AbstractThe objective of this research was to determine the direct influence of self efficacy, job satisfaction, organizational commitment and organizational citizenship behavior (OCB) of  Vocational High Schools Teachers of South Jakarta. The research method using survey with correlation approach, in this study sampled as many as 172 teachers and selected based on a simple random technique (Simple Random Sampling). The research was done in State Vocational High School in the South of Jakarta. Based on the description in the above hypothesis test, then the research findings can be outlined as follows: (1) there is a direct and significant influence between self efficacy with organizational citizenship behavior (OCB), (2) there is direct and significant influence of job satisfaction with organizational citizenship behavior (OCB), (3) there is a direct significant influence between organizational commitment with organizational citizenship behavior (OCB), (4) there is direct and significant influence between self efficacy with organizational commitment, (5) there is direct and significant influence between job satisfaction with organizational commitment, and (6) there is direct and significant influence between self efficacy with job satisfaction.